2010
DOI: 10.1007/s12072-010-9206-2
|View full text |Cite
|
Sign up to set email alerts
|

Rebleeding rates following TIPS for variceal hemorrhage in the Viatorr era: TIPS alone versus TIPS with variceal embolization

Abstract: Purpose To compare rebleeding rates following treatment of variceal hemorrhage with TIPS alone versus TIPS with variceal embolization in the covered stent-graft era. Methods In this retrospective study, 52 patients (M:F 29:23, median age 52 years) with hepatic cirrhosis and variceal hemorrhage underwent TIPS insertion between 2003 and 2008. Median Child-Pugh and MELD scores were 8.5 and 13.5. Generally, 10-mm diameter TIPS were created using covered stent-grafts (Viatorr; W.L. Gore and Associates, Flagstaff, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…[7][8][9][22][23][24][25] Among these routes, TIPS and percutaneous transhepatic access are the two most commonly used access routes. Compared with the TIPS access, the percutaneous transhepatic access offers direct access to the portal vein along the long axis of the portal vein and allows easier access to the peripheral intrahepatic portal vein branches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][22][23][24][25] Among these routes, TIPS and percutaneous transhepatic access are the two most commonly used access routes. Compared with the TIPS access, the percutaneous transhepatic access offers direct access to the portal vein along the long axis of the portal vein and allows easier access to the peripheral intrahepatic portal vein branches.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Various materials are used for embolization of tracts in the liver parenchyma after portal vein manipulation, including gelatin sponge particles, biological tissue adhesives, coils and vascular plugs. [10][11][12][13][23][24][25] The most commonly used embolic materials for the closure of percutaneous portal vein access tracts are coils and gelatin sponge particles; however, they have their own drawbacks. With the use of gelatin sponge particles, incomplete tract embolization or delayed bleeding may occur owing to its soluble and impermanent nature.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant use of variceal embolization during TIPS procedure is theoretically advocated by previous studies in which percutaneous transhepatic variceal embolization could reduce the recurrence of varices and variceal bleeding . Indeed, several researchers suggested that TIPS in combination with embolotherapy of gastroesophageal collateral vessels could lower the rate of rebleeding in comparison with TIPS alone . However, other researchers found a similar incidence of variceal rebleeding between the two groups .…”
Section: Introductionmentioning
confidence: 99%
“…ing rates after TIPS [37]. Because of the fragile nature of thin-walled varices, catheterization using 5-French systems and embolization with 0.035-inch-diameter coils may occasionally result in catheter-or wire-related vessel trauma and contrast extravasation if operators are too forceful during manipulation of these devices (Fig.…”
Section: Gaba Et Almentioning
confidence: 99%